The full recognition of Japan : - Porter, Robert P. (Henry Frowde, 1911)
This book, "The full recognition of Japan, being a detailed account of the economic progress of the Japanese empire to 1911. 1", by Robert P. Porter, is a replication of a book originally published before 1911. It has been restored by human beings, page by page, so that you may enjoy it in a form as close to the original as possible. This book was created using print-on-demand technology. Thank you for supporting classic literature.